2021
DOI: 10.1186/s42523-021-00106-3
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the bovine reproductive tract metagenomes using culture-independent approaches: a systematic review

Abstract: Undesirable microbial infiltration into the female bovine reproductive tracts, for example during calving or mating, is likely to disturb the commensal microflora. Persistent establishment and overgrowth of certain pathogens induce reproductive diseases, render the female bovine reproductive tract unfavourable for pregnancy or can result in transmission to the foetus, leading to death and abortion or birth abnormalities. This review of culture-independent metagenomics studies revealed that normal microflora in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 131 publications
3
31
0
4
Order By: Relevance
“…Histophilus was described as an obligate commensal member in bovine genital mucosal surfaces as well as an opportunistic pathogen under favorable conditions ( Bisgaard, 1995 ; Sandal and Inzana, 2010 ). On the other hand, genus Brucella and Ochrobactrum were not reported as the top abundant genera in other bovine vaginal metagenomic studies ( Jeon and Galvão, 2018 ; Ong et al, 2021 ). Genus Burkholderia in bovine vaginal metagenome was identified as the indicator of exposure to toxic fescue, which is associated with reduced reproductive success ( Ratton et al, 2018 ).…”
Section: Discussionmentioning
confidence: 70%
“…Histophilus was described as an obligate commensal member in bovine genital mucosal surfaces as well as an opportunistic pathogen under favorable conditions ( Bisgaard, 1995 ; Sandal and Inzana, 2010 ). On the other hand, genus Brucella and Ochrobactrum were not reported as the top abundant genera in other bovine vaginal metagenomic studies ( Jeon and Galvão, 2018 ; Ong et al, 2021 ). Genus Burkholderia in bovine vaginal metagenome was identified as the indicator of exposure to toxic fescue, which is associated with reduced reproductive success ( Ratton et al, 2018 ).…”
Section: Discussionmentioning
confidence: 70%
“…Only a few information from metagenomic bacterial characterizations are reported, if any. Most metagenomic studies on the bovine reproductive tract are relevant for vaginal or uterine specimens [ 25 ]. The commonly identified bacterial phyla in bovine female reproductive tracts are represented by Bacteroidetes, Firmicutes and Proteobacteria, followed by Actinobacteria and Fusobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Some of them correspond to the phyla that were detected in our study on bovine semen. Bacteria from these phyla were reported to be present regardless of the breed, farm, gender, geographical location, sampling site, reproductive status or reproductive health [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the bovine vaginal metagenomic studies, DNeasy Blood and Tissue extraction kit (DNeasy) was incorporated for metagenome DNA extraction ( 41 ). However, the benefits of effective host depletion for metagenomic studies were reported, primarily for human clinical samples ( 42 45 ).…”
Section: Introductionmentioning
confidence: 99%